The Politics of Related Lending - Halling, Michael; Pichler, Pegaret; Stomper, Alex (Journal of Financial and Quantitative Analysis, 2016)
Abstract We analyze the profitability of government-owned banks’ lending to their owners, using a unique data set of relatively homogeneous government-owned banks; the banks are all owned by similarly structured local governments in a single country. Making use of a natural experiment that altered the regulatory and competitive environment, we find evidence that such lending was used to transfer revenues from the banks to the governments. Some of the evidence is particularly pronounced in localities where the incumbent politicians face significant competition for reelection.